N-acetylcysteine in high-sucrose diet-induced obesity: Energy expenditure and metabolic shifting for cardiac health - Barbosa Novelli, Ethel Lourenzi [UNESP]; Santos, Priscila Portugal [UNESP]; Assalin, Heloisa Balan [UNESP]; Souza, Gisele [UNESP]; Rocha, Katiucha [UNESP]; Ebaid, Geovana Xavier [UNESP]; Ferreira Seiva, Fabio Rodrigues [UNESP]; Mani, Fernanda [UNESP]; Fernandes, Ana Angelica [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2009)
To study the effects of N-acetylcysteine (NAC, C(5)H(9)-NO(3)S) on high-sucrose diet-induced obesity and its effects on energy metabolism and cardiac oxidative stress, male Wistar 24 rats were divided into four groups (n = 6): (C) given standard chow and water; (N) receiving standard chow and 2 g/l N-acetylcysteine in its drinking water; (HS) given standard chow and 30% sucrose in its drinking water, and (HS-N) receiving standard chow, 30% sucrose and N-acetylcysteine in its drinking water.After 30 days of the treatment, obesity was evidenced in HS rats from enhanced body weight, respiratory quotient, hypertriglyceridemia. As well depressed resting metabolic rate, and oxygen consumption per surface area. HS rats had triacylglycerol accumulation, oxidative stress and metabolic shifting in cardiac tissue. NAC enhanced fat oxidation and energy expenditure, normalizing these adverse effects, comparing HS-N and HS rats. The beta-hydroxyacyl coenzymne-A dehydrogenase activity was higher in HS-N animals, indicating higher heart fatty acid degradation than in HS. NAC normalized myocardial glycogen and lactate dehydrogenase activity, comparing HS-N and HS rats, but had no effects on calorimetric and biochemical parameters in standard-fed rats, comparing N and C groups.In conclusion, N-acetylcysteine offers promising therapeutic value in prevention of high-sucrose induced-obesity and its effect on cardiac tissue. N-acetylcysteine reduced the oxidative stress and prevented the metabolic shifting in cardiac tissue, enhancing fatty acid oxidation and reducing anaerobic metabolism in high-sucrose-fed conditions. The application of this agent in food system via exogenous addition may be feasible and beneficial for antioxidant protection and energy metabolism in cardiac tissue. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cardiac tissue; High-sucrose diet; N-acetylcysteine; Energy metabolism; Oxidative stress